Similarity transformations of heat and mass transfer effects on steady MHD free convection dissipative fluid flow past an inclined porous surface with chemical reaction (Journal of Naval Architecture and Marine Engineering, 2014)
This paper concerns with a steady two-dimensional flow of an electrically conducting incompressible dissipating fluid over an inclined semi-infinite porous surface with heat and mass transfer in presence of chemical reaction. The flow is permeated by a uniform transverse magnetic field. A scaling group of transformations is applied to the governing equations. The system remains invariant due to some relations among the parameters of the transformations. After finding three absolute invariants, a third-order ordinary differential equation corresponding to the momentum equation, and two second-order ordinary differential equations corresponding to energy and diffusion equations are derived. The coupled ordinary differential equations along with the boundary conditions are solved numerically. The effects of various parameters on velocity, temperature and concentration fields as well as skin-friction, Nusselt number and Sherwood number are presented graphically and in tabulated form. DOI: http://dx.doi.org/10.3329/jname.v11i2.18313